1995
DOI: 10.1063/1.359931
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ion species and target temperature on topography development on ion bombarded Si

Abstract: The production of periodic ripple or wavelike structure by Si+, Ne+, Ar+ and Xe+ high-fluence ion bombardment at 20 and 30 keV of Si at 45° incidence angle and at target temperatures from 120 K to room temperature and observed by scanning electron and atomic force microscopy is described. Different species exhibit different behaviors at different temperatures with Xe+ producing transverse wave structures at room temperature and below, Ar+ producing more patchy ripple structures, and Ne+ and Si+ only producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 26 publications
3
17
0
2
Order By: Relevance
“…This suggests that some dependence of u c might exist with the ion species and the energy range. A relation could also exist with very early reports on the dependence of the pattern properties with the target temperature for the case of Ar þ and Ne þ irradiations [17,86]. In these cases, it was necessary to reduce the temperature in order to pattern the surface with lighter ions, in contrast e.g.…”
Section: Medium-energy (10-200 Kev)mentioning
confidence: 72%
See 2 more Smart Citations
“…This suggests that some dependence of u c might exist with the ion species and the energy range. A relation could also exist with very early reports on the dependence of the pattern properties with the target temperature for the case of Ar þ and Ne þ irradiations [17,86]. In these cases, it was necessary to reduce the temperature in order to pattern the surface with lighter ions, in contrast e.g.…”
Section: Medium-energy (10-200 Kev)mentioning
confidence: 72%
“…Obviously, without beam scanning the surface would be expected to reach higher temperatures than when the ion beam is scanned. Moreover, the early results by Carter et al [17,86] on the role of the target temperature further indicate the importance of this variable. Here, it was found that reducing the target temperature below room temperature promoted the initiation and evolution of roughening (patterning) at lower fluences.…”
Section: Medium-energy (10-200 Kev)mentioning
confidence: 90%
See 1 more Smart Citation
“…С точки зрения аэродинамики интересна поверхность с периодической структурой гребней, которая образуется при распылении поверхности наклонным пучком ионов в определенном интервале температу-ры, зависящем от вида и энергии иона [23]. Поскольку в большинстве случаев необходимый интервал -это температуры ниже комнатной, то для получения такой структуры необходимо охлаждение мишени.…”
Section: планируемые работыunclassified
“…[19][20][21][22][23] Ripple formation during oblique angle irradiation on technologically important Si surfaces has begun in large magnitude by the studies of Carter and Vishnyakov. 24,25 Furthermore, nanodot formation study by Gago et al 26 on Si surfaces under normal incidence has generated a new view on pattern formation at the nano scale. Ozaydin et al 27 observed that the surface remains flat at normal incidence ion bombardment under ultra-high vaccum condition which was contradicting the observation of Gago et al 26 These observations strongly suggest that the nanopattern observed in earlier experimental reports on Si surface was due to the unintentionally deposited impurities.…”
mentioning
confidence: 99%